Pendekatan Hermeneutika Kontemporer dalam Penafsiran Al-Qur’an: Menjembatani Eksposisi Tradisional dan Konteks Modern - Shohib, Muhammad (Journal of Knowledge and Collaboration, 2025)
Contemporary hermeneutical approaches to Quranic interpretation have emerged as a dynamic response to the evolving intellectual and social contexts faced by Muslim societies worldwide. This study employs a qualitative methodology, utilizing literature review and library research, to critically examine how modern hermeneutics seeks to bridge the gap between traditional exegesis (tafsir) and the demands of present-day contexts. The analysis highlights that while classical tafsir—rooted in linguistic, historical, and jurisprudential traditions—remains foundational, it often struggles to address contemporary issues such as gender justice, pluralism, and socio-political change. Modern hermeneutical scholars, including Fazlur Rahman and Nasr Hamid Abu Zayd, have introduced contextual and critical frameworks that emphasize the socio-historical background of revelation, the dialogical relationship between text and reader, and the necessity of interpreting the Qur’an in light of current realities. This study finds that the integration of hermeneutical methods enables a more inclusive and adaptive interpretation, fostering relevance without undermining textual integrity. However, it also identifies ongoing debates regarding the legitimacy, boundaries, and potential risks of such approaches, particularly concerning the authority of traditional scholarship. Ultimately, the research demonstrates that contemporary hermeneutics, by engaging both tradition and modernity, offers a promising paradigm for meaningful Quranic interpretation, capable of addressing the complexities of modern Muslim life while maintaining fidelity to the sacred text. This synthesis contributes to the ongoing discourse on Islamic thought, suggesting pathways for future interpretive scholarship.